Full symptomatic recovery does not ensure full recovery of muscle‐tendon function in patients with Achilles tendinopathy - Silbernagel, Karin Grävare (BMJ Group, 2007)
OBJECTIVE: To assess the relationship between muscle‐tendon function and symptoms in patients with Achilles tendinopathy using a validated test battery. DESIGN: A prospective non‐randomised trial. SETTING: Orthopaedic Department, Sahlgrenska University Hospital, Sweden. PATIENTS: 37 patients with a clinical diagnosis of Achilles tendinopathy in the midportion of the tendon, with symptoms for >2 months, were evaluated at the initiation of the study and after 1 year. INTERVENTION: The patients were treated using a rehabilitation programme, under the supervision of a physical therapist, for 6 months. MAIN OUTCOME MEASUREMENTS: The patients were evaluated using the Swedish version of the Victorian Institute of Sports Assessment—Achilles questionnaire (VISA‐A‐S) for symptoms, and a test battery for evaluation of the lower leg muscle‐tendon function. RESULTS: There were significant improvements in the VISA‐A‐S score (p<0.00, n = 37) and the test battery (p<0.02, n = 19) at the 1‐year follow‐up. The VISA‐A‐S questionnaire had an effect size of 2.1 and the test battery had an effect size of 0.73. A low correlation (r = 0.178, p>0.05) was found between the VISA‐A‐S score and the test battery. A high correlation (r = 0.611, p<0.05) was found between the drop counter movement jump and the VISA‐A‐S score. All other tests in the test battery had low correlations (r = −0.305 to 0.155, p>0.05) with the VISA‐A‐S score. Only 25% (4/16) of the patients who had full symptomatic recovery had achieved full recovery of muscle–tendon function as measured by the test battery. CONCLUSION: Full symptomatic recovery in patients with Achilles tendinopathy does not ensure full recovery of muscle–tendon function. The VISA‐A‐S questionnaire and the test battery are sensitive to clinically relevant changes with treatment and can be recommended for use in both the clinic and research.